Failure of ALL recognition by CAR T cells: a review of CD 19-negative relapses after anti-CD 19 CAR-T treatment in B-ALL - Aparicio-Pérez, Clara; Carmona, MDolores; Benabdellah, Karim; Herrera, Concha (Frontiers in Immunology, 2023)
The use of chimeric antigen receptor (CAR) T lymphocytes in the treatment of refractory or relapsed (R/R) B cell acute lymphoblastic leukemia (B-ALL) has meant a radical change in the prognosis of these patients, whose chances of survival with conventional treatment are very low. The current probability of event-free survival by R/R B-ALL patients treated using anti-CD 19 CART cell therapy is as high as 50-60% at 1.5 years, which is a very important advance for this group of very ill patients. Although most patients (70 to 94%) achieve complete remission (CR), the main problem continues to be relapse of the disease. Most relapses, both in clinical trials and real-world evidence, are due to failure of CAR-T cell expansion or limited CAR-T persistence. However, despite the adequate functioning of infused CART lymphocytes, the tumor cells of an important group of patients manage to evade CAR-T attack, resulting in a CD 19-negative relapse. Several mechanisms have been described that may be able to produce the escape of leukemic cells, such as acquired mutations and alternative splicing of the CD19 antigen, CD19 epitope loss or masking, leukemia lineage switching, and trogocytosis. In the present review, we comprehensively analyze the leukemic cell escape mechanisms, the incidence of CD19-negative relapse reported in clinical trials and real-world evidence (outside clinical trials), and provide an update on the main lines of current research into the prevention of leukemia evasion.